(untitled) (The Pakistan Development Review, 2016)
The governance crisis of Pakistan‘s public sector is wide, deep and historically imbedded. There are a host of factors which contribute at varying degrees towards the extant of governance mess. The body of scholarship created to analyse the underlying factors of public sector management mess of Pakistan is not only scant but also deficient in quality, coverage and construct validity. In the entire administrative morass of Pakistan, the quagmire of Federal Board of Revenue (FBR)—house of the state‘s extractive function—is by far the most sombre and serious one. The paper picks up FBR as the unit of analysis and there too, only one variable, that is, appointment of a non-professional generalist as its Chairman to analyse below par performance of Pakistan‘s revenue function—by far the lowest in the world. It posits that appointment of non-professional Chairman, FBR, is a compelling exposition of a collusive duopoly arrangement between elites and generalist cadres of Pakistan civil services—both symbiotically pursuing their perverse particularistic interests at the expense of citizenry at large. The paper develops a theoretical framework within which it attempts to analyse domination of Pakistan‘s extractive function over history from various dimensions. It argues that, since the entire institutional infrastructure of the state has fallen hostage to elitesgeneralist duopoly paradigm, the control of its extractive function is only a logical consequence thereof, and that a non-professional generalist chairman is imposed on the revenue function only to precisely, and fully control the extractive policy formulation process as well as the extractive operations on the ground—to the ultimate advantage of the duopoly. JEL Classification: H1 Keywords: Public Sector Management, Federal Board of Revenue, Civil Service of Pakistan, Inland Revenue Service, Chairman, FBR, Institutionalism